Pengaruh Pengetahuan Tentang Manfaat Tabir Surya Terhadap Perilaku Penggunaan Tabir Surya pada Siswa Siswi SMA Dewi Sartika Jakarta - Neneng Siti Silfi Ambarwati; Dwi Atmanto; Auriah Isahsyah Nathania (EduInovasi: Journal of Basic Educational Studies, 2025)
The negative impact caused by prolonged exposure to the sun's UV rays causes health problems and other skin losses. The skin has a layer of melanin that can protect the skin from the sun's UV rays, including the facial skin, which tends to be more sensitive than other parts of the skin. One way to protect facial skin is by using sunscreen. Dewi Sartika High School is located in Jakarta. The climate of Jakarta is a tropical climate with a rainy season and a dry season. Students of SMA Dewi Sartika Jakarta really need to protect their facial skin from exposure to the sun's UV rays, moreover students of SMA Dewi Sartika Jakarta do a lot of outdoor activities with examples of sports, ceremonies, and extracurricular activities. This study was conducted to determine the effect of knowledge of the benefits of sunscreen on sunscreen use behavior. Sampling on 19 questions about knowledge and 20 statements about behavior. The results showed that between the knowledge variable (X) and the behavior variable (Y) (P=0.0898) so it can be concluded that Ha is rejected and Ho is accepted. This states that there is no significant influence between knowledge on usage behavior.